Study of the genus Gomphocerippus (Orthoptera, Acridoidea, Acrididae, Gomphocerinae) with a new species from northeast China - Li, Jun-Jian; Ren, Bing-Zhong; Li, An (Zootaxa, 2016)
A new species Gomphocerippus longipennis Li & Ren sp. nov. of the genus Gomphocerippus Roberts, 1941 is described and illustrated from the most northern region of China. The new species is allied to Gomphocerippus rufus (Linnaeus, 1758), but differs from the latter by length of lateral foveola 3.0 times width, tegmina partially surpassing the apex of hind femur, costal area of tegmina in male 1.5 times of subcostal area in width and media area of tegmina in male 1.2 times cubital area in width. The type specimens are deposited in the Jilin Provincial Key Laboratory of Animal Resource Conservation and Utilization, Northeast Normal University, Changchun, Jilin, China.